Correlation Between Tuberculosis Type and Comorbidities with Nutritional Recovery Rates Post-Tuberculosis Treatment in Pediatric Patients - Amelia, Safira; Kaswandani, Nastiti (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2024)
Background: Tuberculosis remains a significant cause of mortality in children. Nutritional status is one of the major risk factors for tuberculosis severity. This study investigated the factors influencing nutritional status in tuberculosis patients. Methods: This is a retrospective, cross-sectional study conducted in the tertiary national-referral hospital in Jakarta, Indonesia. Data were obtained from electronic health records from 2012-2018. This study included patients aged 0-18 years-old who were diagnosed and treated with anti-tuberculosis drugs. Patients who did not complete the therapy for minimum 2 months were excluded. Results: A total of 207 patients were included in this study. The type of tuberculosis was associated with the nutritional status of children after 2 months of treatment (p value = 0.014; 95% CI = 0.422 - 0.914). Children with extrapulmonary TB showed better improvement in nutritional status compared to those with pulmonary TB. Comorbidities were also associated with nutritional status (p-value = 0.020; CI95% = 1.063 - 2.382). Patient without comorbidities experience better nutritional status improvement than those with comorbidities. Conclusion: The nutritional status of tuberculosis patients improved after the 2-months of treatment. The type of tuberculosis and the presence of comorbidities influence the outcomes of nutritional status during anti-tuberculosis treatment.